2002
DOI: 10.1590/s0004-27302002000400013
|View full text |Cite
|
Sign up to set email alerts
|

Vias de Sinalização da Insulina

Abstract: RESUMOA insulina é um hormônio anabólico com efeitos metabólicos potentes. Os eventos que ocorrem após a ligação da insulina são específicos e estritamente regulados. Definir as etapas que levam à especificidade deste sinal representa um desafio para as pesquisas bioquímicas, todavia podem resultar no desenvolvimento de novas abordagens terapêuticas para pacientes que sofrem de estados de resistência à insulina, inclusive o diabetes tipo 2. O receptor de insulina pertence a uma família de receptores de fatores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
36

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 56 publications
(46 reference statements)
2
21
0
36
Order By: Relevance
“…A way to control the insulin resistance would be to increase the expression of IRS-2, which partially compensates the lower amount of IRS-1, allowing a regulation of glucose levels in fetal organism, so that hyperglycemia does not happen 12 Analyzing the IGF-IRβ levels, we found that it is increased in the liver and intestine of fetuses with gastroschisis, similar results were found on the IUGR model in rats 14 . In a fetal sheep model, it was also found an increased IGF-IRβ, although on skeletal muscles, suggesting that the increase is a response to low circulating hormone concentrations in fetuses with IUGR 13 .…”
Section: Western Blottingsupporting
confidence: 81%
See 1 more Smart Citation
“…A way to control the insulin resistance would be to increase the expression of IRS-2, which partially compensates the lower amount of IRS-1, allowing a regulation of glucose levels in fetal organism, so that hyperglycemia does not happen 12 Analyzing the IGF-IRβ levels, we found that it is increased in the liver and intestine of fetuses with gastroschisis, similar results were found on the IUGR model in rats 14 . In a fetal sheep model, it was also found an increased IGF-IRβ, although on skeletal muscles, suggesting that the increase is a response to low circulating hormone concentrations in fetuses with IUGR 13 .…”
Section: Western Blottingsupporting
confidence: 81%
“…This situation can be observed in chronic or acute inflammatory states, when there is release of pro-inflammatory cytokines such as interleukin 1 (IL-1), tumor necrosis factor alfa (TNF-α), and interferon gama (IFN-γ). These phosphorilation in serine residues determines a decreased efficacy in the trophic and metabolic pathways and, consequently, changes in the triggers for growth, replication, and development of cellular organelles 7,12 .…”
Section: Western Blottingmentioning
confidence: 99%
“…Prolonged hyperglycemia of patients provokes multiple disorders, causing failure of multiple organs 33 . The streptozotocin-induced model of diabetes in rats causes similar metabolic changes to type 1 diabetes Mellitus 33,34 . The diabetic animals in the present study presented hyperglycemia, reduced body weight gain, polydipsia and increase in plasma levels of fructosamine, confirming the effectiveness of the drug in establishing the diabetes model.…”
Section: Discussionmentioning
confidence: 99%
“…19 A seguir, são apresentados alguns mecanismos envolvidos no favorecimento do aumento de peso e no acúmulo de tecido adiposo após o nascimento, decorrentes ou não da evidente restrição do crescimento fetal. ao aumento dos níveis circulantes de glicose após as refeições, 20 sendo um dos principais fatores de crescimento tanto intra quanto extraútero. Entre suas funções a principal é a captação da glicose sanguínea circulante para armazenamento deste substrato em forma de energia.…”
Section: Aceleração Do Ganho De Pesounclassified
“…20 Porém, a redução de proteínas transportadoras de glicose e sinalizadoras de insulina no músculo esquelético, permite a suposição que, estes indivíduos apresentam ao mesmo tempo um estado de hiperglicemia e resistência insulínica o que favorece a lipogênese.…”
Section: Aceleração Do Ganho De Pesounclassified